Nitric oxide: Is it the cause of muscle soreness? - Radak, Z.; Naito, H.; Taylor, A. W.; Goto, S. (Nitric Oxide, 2015)
Skeletal muscle hosts all of the isoforms of nitric oxide synthase (NOS). It is well documented that nitric oxide (NO) regulates force generation and satellite cell activation, and therefore, damage repair of skeletal muscle. NO can also activate nociceptors of C-fibers, thereby causing the sensation of pain. Although delayed-onset of muscle soreness (DOMS) is associated with decreased maximal force generation, pain sensation and sarcomere damage, there is a paucity of research linking NO and DOMS. The present mini-review attempts to elucidate the possible relationship between NO and DOMS, based upon current literature.